گونجانى خێزانى لاى بەساڵاچووان توێژينەوەيەكى مەيدانييە لە هەرێمى كوردستان/ عێراق - صابر, پ. د. نيان نامق; نورى, م. عادل محمد (Sulaimani Journal for Humanities, 2023)
Social adjustment among the elderly is a modern and contemporary subject in the field of sociology, family adjustment is an important dimension of social adjustment, this research attempts to present the level of family adjustment of the elderly, the aim of the study was to show the level of family adjustment and to discover the degree of family adjustment according to the variables (age, gender, education, marital status) the research was conducted using a analytic survey which is a method of social survey. The sample of the research consisted of elderly residents of the Iraqi Kurdistan Region who are over (60) years old. The results show that family adjustment is high among the elderly, family adjustment changes with age and marriage status, there is no difference in family adjustment between males and females, and family adjustment decreases with higher educational level among the elderly.
Keywords: (Adjustment; Family Adjustment; Family; Social Adjustment; Elderly)